Apertura política y descentralización fiscal en México: el papel de los gobernadores - Víctor Manuel Figueras Zanabria (Nuevo mundo - Mundos Nuevos, 2009)
This paper analyses why the Mexican fiscal system remains highly centralised in spite of the process of political openness. The argument is that Mexican state governors perceive that there is a political cost for unpopular fiscal decisions, which negatively impact the future of their careers. This paper provides empirical evidence about the political careers of Mexican governors and identifies a traditional pattern, which suggests that governors have been excluded from the top positions of the political hierarchy. There is also evidence of the discretionary power of the president to remove governors from their offices.In a second section, the paper explains how the process of political openness weakened the presidential mechanisms of control over the governors, how new and better conditions for their careers arose, and how governors and parties started to behave strategically in a context of high electoral competition. The analysis shows that the new conditions of the political system effectively increased the power of governors, but they have use it to obtain more resources from the federal government instead of negotiating a new and more decentralised fiscal system.